A INVERNADA PAIOL DE TELHA E A NOVA LEGISLAÇÃO QUILOMBOLA (1975-2015) - Cararo, Adriana Ribas Adriano (2016)
ABSTRACT: The Wintering Armory Quilombola community of Tile was founded in 1868, when the Group of thirteen freed slaves took over the land area of Wintering Armory of tile, located in the municipality of Reserva do Iguaçu, Paraná, left in inheritance to the same, by his former mistress, Balbina Francisca de Siqueira, as testament dating from 1860. Currently the community is composed of about 350 families, which are divided into four nuclei (Guarapuava, pinion, Settlement and Embankment), waiting for the completion of the process of titling their territory, initiated in 2005, Is by the INCRA. Since they had to leave their land in 1975, the community sought to retrieve them, promoting several lawsuits, without, however, succeed. The last alternative fetched then, like so many other Rural Black Communities, fighting to be recognised, respected and kept the areas that traditionally occupy, went to fitness for existing legislation. Article 68 ADCT, included in the Federal Constitution of 1988, after mobilization of the black movement, ensures permanent land titling that are occupying the remaining Quilombo Communities calls. After signing the Decree 4,887/2003, communities such as the Wintering Armory of tile that were no longer in their land, have been given the right to have them in physical form, using the principle of attribution. In this way, this work aims to show the importance the quilombola legislation, principally the Decree 4,887, has for these black rural communities, which for years struggling to get possession of the Earth.